Influence of electronic devices on sleep and cognitive performance during athlete training camps - Jones, M. J.; Dawson, B.; Eastwood, P. R.; Halson, S. L.; Miller, J.; Murray, K.; Dunican, I.; Landers, G.; Peeling, P. (The Journal of Strength and Conditioning Research, 2021)
This study investigated the effects of removing athletes' electronic devices in the evening on sleep and performance during training camps. Water polo athletes (n = 26) attending a 7-night training camp (study 1) and triathletes (n = 23) attending a 4-night training camp (study 2) were randomly allocated to a no-device group (no electronic devices could be used after dinner or overnight; ND) or control group (unrestricted electronic device use; CON). Sleep was monitored through wrist actigraphy. The ND group completed a questionnaire measuring anxiety related to being unable to use electronic devices ("nomophobia"). Triathletes also completed a psychomotor vigilance test (PVT) at the start and end of camp. Water polo ND athletes went to bed earlier and spent longer time in bed than CON on the first night, but not on other nights. In triathletes, sleep quantity was not different between groups on any night. No statistically significant differences were observed for changes in nomophobia from the first to the last night of camp. No differences in PVT performance were observed between ND and CON triathletes. In conclusion, removal of evening electronic devices does not improve sleep quantity or cognitive performance in athletes during short-duration (4-7 nights) training camps.